2013
DOI: 10.2166/wst.2013.694
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of waste thermal waters by ozonation and nanofiltraton

Abstract: After their use for heating, e.g. in greenhouses, waste thermal waters may cause environmental problems due to their high contents of ions, and in some cases organic matter (associated with an oxygen demand) or toxic compounds. The aims of this work were to decrease the high organic content of waste thermal water by a combination of ozone treatment and membrane separation, and to investigate the accompanying membrane fouling. The results demonstrated that the chemical oxygen demand and the total organic conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although, in general, used thermal water is known to have a potentially harmful environmental impact (e.g. heat and salt load; Benz et al 2017;Farsang et al 2015;Kiss et al 2013), little remains to be known about the level of their pharmaceutical contamination, as there are few reports on PhAC contamination of used thermal watersourced surface water. A related test was carried out by Avar et al (2016a, b); it revealed the existence of EE2 (0.52 ng L −1 ) and other hormones (drospirenone, levonorgestrel, progesterone; 1.26-2.28 ng L −1 ) in the Hévíz-Páhoki Canal, which is fed by Lake Hévíz, one of the largest thermal lakes in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in general, used thermal water is known to have a potentially harmful environmental impact (e.g. heat and salt load; Benz et al 2017;Farsang et al 2015;Kiss et al 2013), little remains to be known about the level of their pharmaceutical contamination, as there are few reports on PhAC contamination of used thermal watersourced surface water. A related test was carried out by Avar et al (2016a, b); it revealed the existence of EE2 (0.52 ng L −1 ) and other hormones (drospirenone, levonorgestrel, progesterone; 1.26-2.28 ng L −1 ) in the Hévíz-Páhoki Canal, which is fed by Lake Hévíz, one of the largest thermal lakes in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone is a strong oxidant and microbicide (Derrouiche et al, 2013;Asgari et al, 2013), which can eliminate or decompose many undesirable color, taste, odor, forming compounds, toxic substances and micro-pollutants from water. Since ozone treatment produces a lower level of halogenated disinfection by-products, it has been widely accepted as an alternative technology to chlorination in water treatment (Kiss et al, 2013;Rivera-Utrilla and Sánchez-Polo, 2002). Moreover, ozone oxidation can be used to remove disinfection by-products and microorganisms in water (Kasprzyk-Horden et al, 2003;Chiang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%